2011
DOI: 10.1097/ccm.0b013e31821e8791
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin-guided interventions against infections to increase early appropriate antibiotics and improve survival in the intensive care unit: A randomized trial*

Abstract: Procalcitonin-guided antimicrobial escalation in the intensive care unit did not improve survival and did lead to organ-related harm and prolonged admission to the intensive care unit. The procalcitonin strategy like the one used in this trial cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
253
4
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(271 citation statements)
references
References 39 publications
5
253
4
9
Order By: Relevance
“…The use of procalcitonin [64,144,145] or similar biomarkers may facilitate discontinuance of antibiotics in a patient with clinical improvement, although one recent study failed to show any benefit of daily procalcitonin measurement [146]. Table 4) should be rapidly referred to an intensive care unit (ICU) In 2004, the "Surviving Sepsis Campaign" guidelines recommended the use of EGDT [147] based on one large randomized trial [93].…”
Section: The Empirical Treatment Must Be Optimized When Microbiology mentioning
confidence: 99%
“…The use of procalcitonin [64,144,145] or similar biomarkers may facilitate discontinuance of antibiotics in a patient with clinical improvement, although one recent study failed to show any benefit of daily procalcitonin measurement [146]. Table 4) should be rapidly referred to an intensive care unit (ICU) In 2004, the "Surviving Sepsis Campaign" guidelines recommended the use of EGDT [147] based on one large randomized trial [93].…”
Section: The Empirical Treatment Must Be Optimized When Microbiology mentioning
confidence: 99%
“…Two recent studies tried to establish a PCT-algorithm useful to manage sepsis antimicrobial therapy based on plasma PCT levels changes with conflicting results. Bouadma and colleagues showed that this algorithm could reduce antibiotic exposure without apparent adverse outcomes [13], while Jansen et al showed a prolonged admission to the intensive care units without any improvement in the survival rate [14].…”
Section: Traditional Biomarkersmentioning
confidence: 99%
“…Однако у крайне тяжелых пациентов с сепсисом в отделениях интенсивной терапии ежедневное изме-рение ПКТ и попытка моментального терапевтического реагирования не имела значимого преимущества в срав-нении со стандартной тактикой ведения [43].…”
Section: пкт при менингитеunclassified